2001
DOI: 10.1002/cne.1203
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of opsin, visual arrestin, myosin III, and calmodulin in Limulus lateral eye retinular cells and ventral photoreceptors

Abstract: The photoreceptors of the horseshoe crab Limulus polyphemus are classical preparations for studies of the photoresponse and its modulation by circadian clocks. An extensive literature details their physiology and ultrastructure, but relatively little is known about their biochemical organization largely because of a lack of antibodies specific for Limulus photoreceptor proteins. We developed antibodies directed against Limulus opsin, visual arrestin, and myosin III, and we have used them to examine the distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 62 publications
3
46
0
Order By: Relevance
“…2) and sections of adult L. polyphemus brains (Battelle, unpublished observations) demonstrated that the antibody directed against Lp myosin III not only stained photoreceptor cell bodies but also their axonal projections and terminals. Studies with adult animals had also shown that the arhabdomeral cells of the lateral eye do not stain with this antibody, suggesting the protein to be photoreceptor-specific (Battelle et al, 2001). We used this antibody to explore the architecture of the developing central visual pathway in more detail.…”
Section: Central Projections Of the Lateral And Median Eyesmentioning
confidence: 99%
See 4 more Smart Citations
“…2) and sections of adult L. polyphemus brains (Battelle, unpublished observations) demonstrated that the antibody directed against Lp myosin III not only stained photoreceptor cell bodies but also their axonal projections and terminals. Studies with adult animals had also shown that the arhabdomeral cells of the lateral eye do not stain with this antibody, suggesting the protein to be photoreceptor-specific (Battelle et al, 2001). We used this antibody to explore the architecture of the developing central visual pathway in more detail.…”
Section: Central Projections Of the Lateral And Median Eyesmentioning
confidence: 99%
“…The production and characterization of the antibodies against L. polyphemus (Lp) opsin and Lp myosin III were described in Battelle et al (2001); the antibody against Lp visual arrestin in Battelle et al (2000). Opsin is the protein moiety of the visual pigment rhodopsin, which is responsible for absorbing light and initiating the phototransduction cascade (Smith et al, 1993).…”
Section: Immunohistochemistry With Antibodies Directed Against Myosinmentioning
confidence: 99%
See 3 more Smart Citations